Height matters: from monogenic disorders to normal variation - Durand, Claudia; Rappold, Gudrun (Nature reviews. Endocrinology, 2013)
In this Review, the authors discuss the genetics of height, including examples of rare sequence variants that can result in large effects on height and common variants with small effects on height. The key challenges in discovering further genes associated with height and the transition from gene discovery to mechanistic insights are also outlined.
Gesehen am 05.01.2021